2014
DOI: 10.1016/s2007-1523(14)72005-1
|View full text |Cite
|
Sign up to set email alerts
|

Body image dissatisfaction and suicidal ideation in State of Mexico adolescents students

Abstract: The objective was to determine the relationship between body dissatisfaction and suicidal ideation. The sample consisted of 1504 adolescents with an age range of 12-18 years old, middle or high school students, all residents of Mexico State. The participants answered the BSQ and Beck's Suicidal Ideation Scale; both instruments have validity and reliability for the Mexican population. The results allowed us to observe the highest percentage of body dissatisfaction (22%), suicidal ideation (42%) as well as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In most of the studies found, the percentage of the study sample that presented body dissatisfaction ranged from 50% to 85% of the participants. Only in four studies, 13,21,34,35 dissatisfaction occurred in less than 50% of the sample, in percentages ranging from 20% to 45%.…”
Section: %mentioning
confidence: 88%
See 2 more Smart Citations
“…In most of the studies found, the percentage of the study sample that presented body dissatisfaction ranged from 50% to 85% of the participants. Only in four studies, 13,21,34,35 dissatisfaction occurred in less than 50% of the sample, in percentages ranging from 20% to 45%.…”
Section: %mentioning
confidence: 88%
“…The selected studies have diverse origins, with the majority of the work being carried out in the United States of America [11][12][13][14][15][16] , Mexico, [17][18][19][20][21][22][23][24][25][26] and Africa. [27][28][29][30][31] To a lesser extent, works from Australia, 32 Canada, 33 Spain, 34 China, 35 Chile, 36 and India.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, si un joven no se siente satisfecho con su cuerpo es más probable que realice comportamientos que atenten contra la salud física y psicológica (Raich, 2016). Des-afortunadamente, tal condición no es inusitada en el contexto estudiado, ya que como advierten algunas investigaciones realizadas en México, en el país existe una importante preocupación por el aspecto corporal (Cocca, Blanco, Peinado & Viciana, 2016) y se advierte en algunos casos que la insatisfacción con la imagen del mismo alcanza un 22% de la población adolescente (Guadarrama, Carrillo, Márquez, Hernández y Veytia, 2014).…”
Section: Introductionunclassified
“…A pesar de tales evidencias, la relación entre la insatisfacción con la imagen corporal e ideación suicida ha sido poco investigada en México, no obstante ello, se pueden consignar como antecedentes del presente trabajo algunos hallazgos en estudios previos que manifiestan una correlación entre ambas variables, por ejemplo: en una investigación efectuada en el estado de México por Guadarrama et al (2014) se evidenció que el 13% del total de la población (1054 participantes adolescentes) presentó ideación suicida e insatisfacción con su imagen corporal. Asimismo, indagatorias respecto de la Anorexia o la Bulimia, trastornos alimentarios que se caracterizan por una insatisfacción con la imagen corporal, advierten que estas patologías son factores de riesgo de conducta suicida en escolares (Martínez, Vianchá, Pérez y Avendaño, 2017).…”
Section: Introductionunclassified